The Relationship Between Plasma Progesterone Concentration on Day 6 After Artificial Insemination and Pregnancy Rate of Dairy Cows in Vietnam - N. V. Thanh; P. T. Hang; P. V. Gioi; N. C. Toan; S. T. Long (Faculty of Animal Science, Bogor Agricultural University, 2023)
The study was conducted to determine the relationship between plasma progesterone (P4) concentration on day 6 following artificial insemination (AI) and the pregnancy rate to provide recommendations for measuring P4 concentration before embryo transfer in cows. A total of 85 cows were double AI (day 0) after being detected in natural heat by visual observation. On day 6 after AI, the blood sample was collected from the coccygeal vein to measure plasma P4 concentration by ELISA method. Pregnancy was diagnosed on the 60th day after AI by rectal palpation. The results showed that the plasma P4 concentration at day 6 after AI of the pregnant cow group (4.262±2.195 ng/mL) was significantly higher than that of the non-pregnant cow group (3.146±2.377 ng/mL) (p<0.05). The pregnancy rate was lowest in the group of cows with plasma P4 concentration <2ng/mL, then gradually increased with P4 concentration. The pregnancy rate of cows tended to be stable when P4 concentration ≥4.0 ng/mL. The pregnancy rate of cows was highest when the P4 concentration was from 3-4 ng/mL and 5-6 ng/mL. Additionally, the pregnancy rate of cows is positively correlated with the plasma P4 concentration according to the formula P= 26.356 + 6.612* P4. In conclusion, the plasma concentration of P4 at day 6 after AI has a positive relationship with the pregnancy rate of cows.